Solution reactivity studies of group 15 Zintl anions towards unsaturated substrates - Turbervill, R (2014)
This thesis describes selected reactivity studies of group 15 Zintl anion [E7]3– (E = P, As) derived cages towards a series of unsaturated organic molecules. The synthesis and characterization of forty-two compounds derived from [E7]3– cages are detailed herein. A high yielding procedure for the synthesis of [HE7]2– (E = P, As) from the K3E7 Zintl phase has been developed. This solves prior issues with poor solubility and variable purity of the Zintl phases. The conditions required for the deprotonation of the phosphorus congener to [P7]3– are described. The reactivity of both [P7]3– and [HP7]2– towards carbon dioxide and isolobal isocyanates and carbodiimides was explored. This yielded a series of monofunctionalized [E7R]2– cages, via a net hydropnictination of a C=N double bond of the organic substrate. The protonation chemistry of these anions was further investigated, resulting in the formation of the protic [HP7C(NHDipp)(NDipp)]– cluster. This anion is capable of further hydrophosphination chemistry to give a series of difunctionalized heptaphosphide cages. The reaction of [E7]3– with alkynes results in the formation of the relatively unusual 1,2,3-tripnictolide anions. A series of such anions have been prepared, encompassing all of the previously reported anions and several novel species. Investigation of the coordination properties of these cyclopentadienyl analogues shows that they are superior π acceptor ligands. A synthetic route to [P5]– as a compositionally pure solid, and some initial studies on its protonation chemistry are also additionally presented.